The era of in vivo T cell engineering - Ramos, Gustavo Campos; Hudecek, Michael (Med, 2022)
Cell therapy with genetically engineered T cells has revolutionized the treatment of malignant diseases, but its potential use beyond the realms of oncology has been underexplored. In a recent study, Rurik et al.1 built on the technologies underlying mRNA vaccines to transduce T cells in vivo, harnessing them to target cardiac fibrosis.
CRIS-Team Scopus Importer:2023-03-23